Comparison of Metabolite Content between Water Extract and Ethanol Extract of Moringa Leaves (Moringa oleifera): A Systematic Literature Review - Lia Fikayuniar; Adinda Khairun Nissa; Zulfa, Adiva Nafila; Astriani Nurjanah; Intan Nurcahyani; Neni Nurlelah; Risti Septanti (HM Publisher, 2023)
Extraction with water and ethanol are two common methods used to isolate secondary metabolites from Moringa oleifera. Extraction with water usually produces extracts rich in polar compounds, while extraction with ethanol tends to be better at isolating non-polar compounds. This study aimed to carry out a systematic review related to the comparative study of metabolite content between aqueous extracts and ethanol extracts of Moringa oleifera. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the comparison of the secondary metabolite content of aqueous and ethanol extracts of Moringa oleifera. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. Moringa leaf water extract has higher flavonoid and phenolic content than the ethanol extract of Moringa leaves. Meanwhile, the ethanol extract of Moringa leaves contains higher alkaloids and triterpenoids than the aqueous extract of Moringa leaves.